Quality-of-life outcomes of the ROBOtic-assisted versus Conventional Open Partial nephrectomy (ROBOCOP) II trial - Sidoti Abate, Marie Angela; Menold, Hanna; Neuberger, Manuel; Kirchner, Marietta; Haney, Caelán Max; Nuhn, Philipp; Westhoff, Niklas Christian; Honeck, Patrick; Michel, Maurice Stephan; Kriegmair, Maximilian; Kowalewski, Karl-Friedrich (BJU international, 2024)
OBJECTIVES: To comprehensively compare quality-of-life (QoL) outcomes between open partial nephrectomy (OPN) and robot-assisted PN (RAPN) from the randomised ROBOtic-assisted versus Conventional Open Partial nephrectomy (ROBOCOP) II trial, as QoL data comparing OPN and RAPN are virtually non-existent, especially not from randomised controlled trials (RCTs). PATIENTS AND METHODS: The ROBOCOP II was a single-centre, open-label RCT between OPN and RAPN. The pre-planned analyses of QoL outcomes are presented. Data were analysed descriptively in a modified intention-to-treat population. RESULTS: A total of 50 patients underwent surgery. At postoperative Day 90 (POD90), there was no significant difference for the Kidney Disease Quality of Life-Short Form questionnaire score (mean [sd] OPN 72 [20] vs RAPN 76 [15], P = 0.850), while there were advantages for RAPN in the subdomains of 'Pain' (P = 0.006) and 'Physical functioning' (P = 0.011) immediately after surgery. For the European Organisation for Research and Treatment of Cancer quality of life questionnaire 30-item core there were overall advantages directly after surgery (mean [sd] score OPN 63 [20] vs RAPN 75 [17], P = 0.031), as well as for the subdomains 'Fatigue' (P = 0.026), 'Pain' (P = 0.002) and 'Constipation' (P = 0.045) but no differences at POD90. There were no differences for the EuroQoL five Dimensions five Levels questionnaire at POD90 (mean [sd] score OPN 70 [22] vs RAPN 72 [17], P = 1.0) or at any other time point. Finally, no significant differences were found for the overall Convalescence and Recovery Evaluation questionnaire score at POD90 (mean [sd] OPN 84 [13] vs RAPN 86 [10], P = 0.818) but less pain in the RAPN group (P = 0.017) directly after surgery. CONCLUSIONS: Pain and physical functioning as subdomains of QoL are improved after RAPN compared to OPN in the early postoperative course, while there are no differences anymore after 3 months.
Zuerst veröffentlicht: 24. Mai 2024
Gesehen am 26.09.2024